Implementation Of Corruption Offences As Special Crimes In The Draft Penal Code - Alwandani Alwandani; Yasmirah Mandasari Saragih; Rahul Ardian Fikri (Asosiasi Penelitian dan Pengajar Ilmu Hukum Indonesia, 2024)
Corruption is a problem that needs to be taken seriously and is a legal issue in every country in the world, including Indonesia. The disease of corruption is increasingly rampant. The seriousness of the government in overcoming criminal acts of corruption is the establishment of Law Number 31 of 1999 as amended by Law Number 20 of 2001 concerning Eradication of Corruption Crimes. The formulation of the problem discussed in writing this thesis is Regarding the Application of the Criminal Act of Assistance in corruption. The research method used in writing this thesis is a research method carried out with a Normative Juridical Approach, namely Legal Principles and referring to Legal Norms contained in the library research method (library research), namely conducting research using data from various reading sources such as Laws - Invitations, books, magazines and the internet which are considered relevant to the problems that the author will discuss in this thesis. The assistance of corruption crimes committed by Widjokongko Puspoyo who helped Widjanarko Puspoyo receive gifts from Bulog partners caused Widjokongko Puspoyo to be punished for violating Article 11 Law No. 20 of 2001 concerning changes to Law no. 31 of 1999 concerning the Eradication of Corruption in conjunction with Article 15 of Law no. 31 of 1999 concerning the Eradication of Corruption in conjunction with Article 56 1 of the Criminal Code. Assistance in Corruption Crimes is regulated in Article 15 of Law No. 31 of 1999, in this article it states that the act of assisting corruption will be punished the same as the perpetrators of corruption in accordance with the provisions in Law No. 31 of 1999 as has been amended by Law No. 20 of 2001 concerning the Eradication of Corruption Crimes. In Article 15 Criminal Responsibility for Assistance Crimes in corruption cases is seen from the extent to which the act of assisting the Corruption Crime was carried out. In determining the amount of punishment for the assistant to the criminal act of corruption, it can be seen from the articles violated by the assistant to the criminal act of corruption.